Leadership, conflict, and pedagogy: Examining the role of management in mitigating academic disagreements that affect learning – A qualitative case study design. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Conflict among academic staff is an inevitable part of university life, often arising from competing priorities, power dynamics, and differing pedagogical philosophies. When unresolved, such conflicts can negatively affect collaboration, morale, and ultimately the student learning experience. Leadership and departmental management play a crucial role in either exacerbating or resolving these tensions. This study explores how university leadership intervenes in academic disputes and assesses the impact of these conflicts on teaching and learning within a South African university department. Methods A qualitative case study design was employed. Data were collected through in-depth, semi-structured interviews with 12 academic staff members and 3 faculty managers at a mid-sized South African university. Participants were selected using purposive sampling based on their involvement in or exposure to departmental conflicts. Thematic analysis was conducted following Braun and Clarke’s framework to identify patterns related to leadership, conflict management, and pedagogical disruption. Results Three dominant themes emerged: (1) Leadership Silence and Avoidance, where managers failed to address conflicts early, allowing them to escalate; (2) Pedagogical Disruption, where conflicts led to breakdowns in team teaching and inconsistent student engagement; and (3) Restorative Leadership Practices, where inclusive dialogue, mediation, and clear role boundaries helped restore collaboration. Staff widely agreed that unresolved conflicts affected curriculum coherence, delayed marking, and confused students about academic expectations. Managers who engaged proactively in transparent conflict resolution were credited with improving departmental cohesion and restoring trust. Conclusion Leadership plays a decisive role in managing academic disagreements. Silence or inaction reinforces division, while proactive, inclusive leadership promotes a healthier departmental culture and supports student learning. Recommendations Universities should train academic managers in conflict resolution and implement early-intervention frameworks. Clear communication protocols, mediation practices, and regular reflection spaces should be institutionalized to foster an environment where disagreement does not compromise pedagogy.